2018
DOI: 10.1080/21663831.2018.1546237
|View full text |Cite
|
Sign up to set email alerts
|

Processing of novel pseudomorphic Cu–Mo hierarchies in thin films

Abstract: A new processing route has been discovered through which far-from-equilibrium, metastable architectures with unprecedented properties are synthesized. This novel architecture contains many orders of hierarchy with multiple concentration modulation wavelengths. At one length scale, the matrix is comprised of lateral modulations of BCC Mo and pseudomorphic BCC Cu with a wavelength of 10 nm. FCC, Cu-rich islands of approximate 250 nm diameter are woven in-between the Mo-Cu matrix and contain ordered arrays of pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…The following morphologies were produced with the corresponding temperatures: 23 °C, nanocrystalline Cu and Ta; 400 °C, wavy-layered bicontinuous Cu-Ta oriented perpendicular to the film growth axis; 600 °C, agglomerated Cu surrounded by thin bands of Ta; and 800 °C, larger agglomerations of Cu with trace amounts of Ta trapped inside and Ta bands with trace amounts of Cu trapped inside. The 800 °C morphology is characterized as a hierarchical structure with features on multiple separate length scales as also observed in co-deposited Cu-Mo 16 . Figure 1 presents high angle annular darkfield (HAADF) scanning transmission electron microscopy (STEM) micrographs of cross-sectional samples to illustrate the four disparate film morphologies.…”
mentioning
confidence: 55%
“…The following morphologies were produced with the corresponding temperatures: 23 °C, nanocrystalline Cu and Ta; 400 °C, wavy-layered bicontinuous Cu-Ta oriented perpendicular to the film growth axis; 600 °C, agglomerated Cu surrounded by thin bands of Ta; and 800 °C, larger agglomerations of Cu with trace amounts of Ta trapped inside and Ta bands with trace amounts of Cu trapped inside. The 800 °C morphology is characterized as a hierarchical structure with features on multiple separate length scales as also observed in co-deposited Cu-Mo 16 . Figure 1 presents high angle annular darkfield (HAADF) scanning transmission electron microscopy (STEM) micrographs of cross-sectional samples to illustrate the four disparate film morphologies.…”
mentioning
confidence: 55%
“…Experiments conducted by Derby et al 11 revealed that phase separation during film growth typically gives rise to morphologies that are monolithic in architecture with only one composition modulation (CM) wavelength. The direction of CM can be vertical (along growth direction) or lateral (normal to growth direction) or random (bicontinuous, intertwined).…”
Section: Hierarchical Nanostructuresmentioning
confidence: 99%
“…A colony consists of ultrafine, submicron (~ 220 nm) crystals of α-Zr separated by a 20-nm-thick body-centered-cubic (bcc) Zr interphase (Figure 4d). The α/β interface has a preferred Burgers orientation relationship of (0001)||(011)/[1120]|| [11] (Figure 4e). A geometrically feasible path for slip transfer, therefore, exists, wherein the preferred slip planes of Zr are aligned with the preferred {110} slip planes of β across the α/β interface.…”
Section: Three-dimensional Interfaces and Hcp-based Hierarchical And Heterogeneous Laminatesmentioning
confidence: 99%
“…These concentration modulations are classified as monomodal, maintaining a consistent microstructure morphology throughout the film. Several mesoscale models employed classical thin-film growth theory [3][4][5][6][7][8] to elucidate and understand the relevant kinetic and thermodynamics pathways [9][10][11][12][13], leading to the formation of such monomodal concentration modulation. Recent experimental results present a fourth class of concentration modulation with regions self-organizing into hierarchical microstructures [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Several mesoscale models employed classical thin-film growth theory [3][4][5][6][7][8] to elucidate and understand the relevant kinetic and thermodynamics pathways [9][10][11][12][13], leading to the formation of such monomodal concentration modulation. Recent experimental results present a fourth class of concentration modulation with regions self-organizing into hierarchical microstructures [11,14,15]. These microstructures are multimodal, having multiple, distinct sets of features across several length scales.…”
Section: Introductionmentioning
confidence: 99%